Representações sociais em enfermagem: comentários sobre teses e dissertações - MACHADO, Ana Lúcia (Universidade Federal do Pará, 2018)
The starting point of this work consists on a revision of thesis and dissertations developed by nurses aiming to check how the social representation was used as a theoretical referencial on these researches. Through a sistematic reading of these works some points were dettached, as thematic, main resultas and reflections proposed in order to atain professional practice nursing. It was ascertained from the analysed works that this theoretical referencial is used by nurses, and that some  studies developed introduce significative results from these professionals.